2022
DOI: 10.1093/rb/rbac085
|View full text |Cite
|
Sign up to set email alerts
|

Integrated printed BDNF-stimulated HUCMSCs-derived exosomes/collagen/chitosan biological scaffolds with 3D printing technology promoted the remodelling of neural networks after traumatic brain injury

Abstract: The restoration of nerve dysfunction after traumatic brain injury (TBI) faces huge challenges due to the limited self-regenerative abilities of nerve tissues. In situ inductive recovery can be achieved utilizing biological scaffolds combined with endogenous human umbilical cord mesenchymal stem cells (HUCMSCs)-derived exosomes (MExos). In this study, brain derived neurotrophic factor (BDNF)-stimulated HUCMSCs-derived exosomes (BMExos) were composited with collagen/chitosan by 3D printing technology. 3D-printed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…In vivo experiments on rats demonstrated that 3D-CC-BMExos therapy improved neuromotor and cognitive function in TBI models, facilitated the regeneration of nerve fibers, synaptic connections, and myelin sheaths in TBI lesions [67].…”
Section: Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo experiments on rats demonstrated that 3D-CC-BMExos therapy improved neuromotor and cognitive function in TBI models, facilitated the regeneration of nerve fibers, synaptic connections, and myelin sheaths in TBI lesions [67].…”
Section: Brainmentioning
confidence: 99%
“…Liu et al [67] conducted a study to evaluate scaffolds made of collagen, chitosan, and exosomes derived from human umbilical cord MSCs using 3D printing technology. These scaffolds were referred to as 3D-CC-BMExos and exhibited exceptional mechanical properties and biocompatibility.…”
Section: Brainmentioning
confidence: 99%
“…New insights into the underlying mechanisms of neuroinflammation have prompted the design of novel biomaterials to mitigate the detrimental effects of excessive inflammation and protect surrounding CNS tissue from secondary damage. Recent advances have been made in a variety of biomaterial strategies for modulating neuroinflammation, including nanoparticles with the ability to cross the selectively permeable BBB/ BSCB, [116][117][118] hydrogels that enable controlled delivery of immunomodulatory therapeutics, 119,120 implantable scaffolds with biophysical cues to enhance cellular alignment and promote a growth-permissive environment for neural regeneration, [121][122][123][124][125] and biomaterial coatings to prolong the lifetime of neural probe implants. 32,[126][127][128]…”
Section: Biomaterials For Modulating Neuroinflammationmentioning
confidence: 99%
“…A notable application of this strategy involves the use of biological scaffolds combined with EVs derived from HUCMSCs, specifically engineered for in situ inductive recovery. In a pioneering study by Liu et al, exosomes from BDNF-stimulated HUCMSCs (BMExos) were incorporated into collagen/chitosan scaffolds via 3D printing [ 290 ]. These scaffolds, which have outstanding mechanical properties and biocompatibility, were shown in vivo to significantly improve neuromotor and cognitive abilities in a rat TBI model, demonstrating the promise of integrating exosomes with advanced bio-nanomaterials for neural repair.…”
Section: Applications Of Evs As Nanotheranostic Targets In Cnsmentioning
confidence: 99%